Rancang Bangun Aplikasi Permainan Alat Musik Tradisional Berbasis Android - Khozainuz Zuhri; Fatimah Fahurian; Kusnadi Kusnadi (Jurnal Teknologi dan Informatika (JEDA), 2021)
AbstractGame is something that is used to play which is played with certain rules. Game is a game that uses electronic media, is an entertainment in the form of multimedia that is made as attractive as possible so that players get something so that they get inner satisfaction. But behind these advantages, educational games also have drawbacks, namely very minimal interest from the public in educational games, this is because most users or the public think that the game is boring and uninteresting, and this has become the mindset of the community since this educational game was first introduced. appears, besides programmers who make educational games are still very few compared to programmers who make non-educational games. Therefore, the author proposes an educational game application that can be of interest to students by making the game look as attractive as possible so that when playing the game you can see an attractive appearance. The results of the research are an Android-based application for the introduction of Lampung Province Traditional Musical Instruments which can help people learn more about Lampung traditional musical instruments, besides the system shows that the game application has been running well.